Investigation of Micro-Bending of Sheet Metal Laminates by Laser-Driven Soft Punch in Warm Conditions - Huixia Liu (Micromachines, 2017)
Microscale laser dynamic flexible forming (µLDFF) is a novel ultrahigh strain rate manufacturing technology with high efficiency and low cost. However, the µLDFF is just confined to single-layer foil at present. In this work, sheet metal laminates (Cu/Ni) were selected as the experimental material for its excellent mechanical and functional properties, and a new micro-bending method of sheet metal laminates by laser-driven soft punch was proposed in warm conditions. The micro-mold and warm platform were designed to investigate the effects of temperature and energy on formability, which were characterized by forming accuracy, surface quality, element diffusion, and so on. The experimental results show that the forming accuracy and quality increased first and then decreased with laser energy, but the hardness increased consistently. In warm conditions, the fluidity of material was improved. The forming depth and accuracy increased for the relieved springback, and the surface quality increased first and then decreased. The tensile fracture disappeared with temperature for the decreased hardness and thinning ratio, and the element diffusion occurred. Overall, this study indicates that the formability can be improved in warm conditions and provides a basis for the investigation of micro-bending of sheet metal laminates by µLDFF in warm conditions.